Resin composition, pellets, and molded article

The resin composition addresses thermal stability and impact resistance issues by incorporating a metal salt flame retardant, anti-sagging agent, and specific inorganic particles, ensuring effective flame retardancy and impact resistance across varying conditions.

JP2025008470APending Publication Date: 2025-01-20MITSUBISHI ENG PLASTICS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023110677
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Conventional flame-retardant polycarbonate resin compositions using bromine-based or phosphorus-based flame retardants face issues with thermal stability and reduced heat resistance, and there is a need for compositions that maintain flame retardancy and impact resistance under various environmental conditions, particularly in moist heat and low-temperature environments.

Method used

A resin composition containing polycarbonate resin, a metal salt flame retardant, an anti-sagging agent, and inorganic particles with specific thermal conductivity and particle size, along with a core/shell type graft copolymer elastomer, enhances flame retardancy and impact resistance by effectively managing heat and impact in challenging environments.

Benefits of technology

The composition achieves excellent flame retardancy after moist heat treatment and maintains impact resistance in low-temperature conditions, with improved thermal conductivity and reduced particle size minimizing impact resistance loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008470000001
    Figure 2025008470000001
  • Figure 2025008470000002
    Figure 2025008470000002
  • Figure 2025008470000003
    Figure 2025008470000003
Patent Text Reader

Abstract

To provide a resin composition excellent in flame retardancy after moist heat environment treatment and impact resistance in a low-temperature environment, and to provide pellets and a molded article using the resin composition.SOLUTION: The resin composition contains, based on 100 pts.mass of a polycarbonate resin (A), 0.01 pt.mass or more and 0.3 pt.mass or less of a metal salt flame retardant (B), 0 pt.mass or more and 1 pt.mass or less of a drip inhibitor (C), 0.05 pt.mass or more and 3 pts.mass or less of inorganic particles (D) having a thermal conductivity of 15 W / m K or more and an average particle diameter of 4 μm or less, and 0.01 pt.mass or more and 5 pts.mass or less of an elastomer (E).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, and a molded article, and in particular to a resin composition containing a polycarbonate resin as a main component. [Background technology]

[0002] Polycarbonate resins are resins that are excellent in heat resistance, impact resistance, flame retardancy, transparency, etc., and are used in a wide variety of fields, such as automotive materials, electrical materials, housing materials, etc. In particular, flame-retardant polycarbonate resin compositions are widely used as components for various types of OA information devices, such as computers, notebook personal computers, copiers, printers, and portable devices.

[0003] In the conventional flame-retardant polycarbonate resin composition, a method using a bromine-based flame retardant or a phosphorus-based flame retardant is widely used. However, in the conventional method, the amount of the flame retardant used is large, and the thermal stability of the flame retardant is insufficient, so that the heat resistance and melt stability of the resin composition are reduced. In addition, from the viewpoint of environmental consideration, there is a strong demand for a flame-retardant aromatic polycarbonate resin composition that does not use a bromine-based flame retardant or a phosphorus-based flame retardant.

[0004] On the other hand, a technique for making polycarbonate resin flame-retardant by adding a metal salt flame retardant is known, and in recent years, many improved techniques have been reported as a method for making polycarbonate resin flame-retardant without using bromine-based flame retardants or phosphorus-based flame retardants (Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-002750 A Summary of the Invention [Problem to be solved by the invention]

[0006] Here, there is a demand for flame-retardant polycarbonate resin compositions using metal salt flame retardants that can maintain high performance under a wide range of usage conditions and environments. Specifically, flame retardancy after treatment in a hot and humid environment and impact resistance in a low-temperature environment are required. The present invention aims to solve these problems, and to provide a resin composition having excellent flame retardancy after treatment in a moist and hot environment and excellent impact resistance in a low-temperature environment, as well as pellets and molded articles using the resin composition. [Means for solving the problem]

[0007] In light of the above-mentioned problems, the present inventors have conducted research and have found that the above-mentioned problems can be solved by blending inorganic particles having a thermal conductivity of 15 W / m·K or more and an average particle size of 4 μm or less in a resin composition containing a polycarbonate resin, a metal salt flame retardant, an anti-dripping agent, and an elastomer. Specifically, the above problems were solved by the following means. <1> A resin composition comprising, relative to 100 parts by mass of a polycarbonate resin (A), 0.01 to 0.3 parts by mass of a metal salt flame retardant (B), 0 to 1 part by mass of an anti-dripping agent (C), 0.05 to 3 parts by mass of inorganic particles (D) having a thermal conductivity of 15 W / m·K or more and an average particle size of 4 μm or less, and 0.01 to 5 parts by mass of an elastomer (E). <2> The inorganic particles (D) contain at least one selected from the group consisting of boron nitride, silicon carbide, and silicon nitride. <1> The resin composition according to claim 1. <3> The elastomer (E) comprises a core / shell type graft copolymer. <1> or <2> The resin composition according to claim 1. <4> the mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is 0.03 to 0.5; <1> ~ <3> 10. The resin composition according to claim 9 . <5> the inorganic particles (D) contain at least one selected from the group consisting of boron nitride, silicon carbide, and silicon nitride, the elastomer (E) contains a methyl methacrylate-butadiene copolymer, and a mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is 0.03 to 0.5; <1> ~ <4> 10. The resin composition according to claim 9 . <6> <1> ~ <5> 2. A pellet of the resin composition according to claim 1. <7> <1> ~ <5> 2. A molded article formed from the resin composition according to claim 1. <8> <6> A molded article formed from the pellets according to claim 1. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition having excellent flame retardancy after treatment in a hot and humid environment and excellent impact resistance in a low-temperature environment, as well as pellets and molded articles using the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated. In this specification, the glass transition temperature (Tg, sometimes referred to as the glass transition point) is a value measured by differential scanning calorimetry (DSC) in accordance with ISO11357, unless otherwise specified.

[0010] The resin composition of the present embodiment is characterized in that it contains, relative to 100 parts by mass of polycarbonate resin (A), 0.01 part by mass or more and 0.3 part by mass or less of metal salt flame retardant (B), 0 part by mass or more and 1 part by mass or less of anti-dripping agent (C), 0.05 part by mass or more and 3 parts by mass or less of inorganic particles (D) having a thermal conductivity of 15 W / m K or more and an average particle size of 4 μm or less, and 0.01 part by mass or more and 5 parts by mass or less of elastomer (E). By adopting such a constitution, it is possible to provide a resin composition having excellent flame retardancy after a moist heat environment treatment and excellent impact resistance in a low temperature environment. That is, combustion proceeds when all three elements, namely oxygen, combustibles, and heat, are present in the object to be burned. In this embodiment, it is presumed that by blending inorganic particles having high thermal conductivity, the heat of the three elements is released from the object to be burned, thereby improving the flame retardancy. On the other hand, polycarbonate resin is a resin that is inherently excellent in impact resistance, but when inorganic particles are blended, the impact resistance of the resulting molded product tends to decrease. In this embodiment, it is presumed that the decrease in impact resistance can be effectively suppressed by adjusting the particle size of the inorganic particles. The present invention will be described in detail below.

[0011] <Polycarbonate resin (A)> The resin composition of the present embodiment contains a polycarbonate resin (A). Specifically, the polycarbonate resin (A) is not particularly limited as long as it contains a -[OR-OC(=O)]- unit (wherein R is an organic group, preferably a hydrocarbon group, more preferably an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain. In this embodiment, the polycarbonate resin (A) is preferably an aromatic polycarbonate resin, and more preferably a polycarbonate resin having a bisphenol skeleton. By using such a polycarbonate resin, better heat resistance and toughness are achieved. In this embodiment, the polycarbonate resin having a bisphenol skeleton is preferably a structural unit having a bisphenol skeleton in 90 mol % or more of the total structural units, and more preferably a structural unit derived from bisphenol A in 90 mol % or more of the total structural units.

[0012] The viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 10,000 or more, more preferably 12,000 or more, and even more preferably 15,000 or more. By making it equal to or more than the lower limit, the durability of the molded article obtained tends to be further improved. The upper limit of the viscosity average molecular weight (Mv) of the polycarbonate resin (A) is preferably 50,000 or less, more preferably 40,000 or less, and even more preferably 30,000 or less. By making it equal to or less than the upper limit, the molding processability of the molded article tends to be further improved. The viscosity average molecular weight (Mv) was calculated by using methylene chloride as a solvent and an Ubbelohde viscometer to determine the intrinsic viscosity [η] (unit: dL / g) at 25°C, and then using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 ×Mv 0.83 , means a value calculated from When two or more types of polycarbonate resins are used, the viscosity average molecular weight is the mixture.

[0013] The method for producing the polycarbonate resin (A) is not particularly limited, and polycarbonate resins produced by the conventionally known phosgene method (interfacial polymerization method) or melting method (ester exchange method) can be used. When the melting method is used, a polycarbonate resin having an adjusted amount of OH groups at the terminal groups can be used.

[0014] The polycarbonate resin (A) used in this embodiment may be a recycled polycarbonate resin. In this embodiment, even if a recycled polycarbonate resin is used, excellent performance equivalent to that of a virgin polycarbonate resin can be achieved. Recycled polycarbonate resin means virgin polycarbonate resin that has been subjected to some kind of molding or processing, and includes market collected products, rejected polycarbonate resin molded products, and scraps from the manufacture of polycarbonate resin molded products. Molded products include injection molded products, extrusion molded products, and molded products formed by other methods. Examples of recycled polycarbonate resin include those obtained by material recycling in which recovered used polycarbonate resin molded products are crushed and alkaline washed to be reused as fibers, etc., those obtained by chemical recycling (chemical decomposition method), and those obtained by mechanical recycling. Chemical recycling involves chemically breaking down the collected used polycarbonate resin molded products, returning them to their raw material level and resynthesizing the polycarbonate resin.Mechanical recycling, on the other hand, is a method that makes it possible to remove dirt from polycarbonate resin molded products more reliably than material recycling by carrying out alkaline washing more strictly than in the above-mentioned material recycling, or by vacuum drying at high temperatures. For example, after foreign matter is removed from used polycarbonate resin molded products, the products are crushed and washed, and then pelletized using an extruder to obtain recycled polycarbonate resin. Examples of used polycarbonate resin molded articles include disks, sheets (including films), meter covers, headlamp lenses, and bottles.

[0015] For details of the polycarbonate resin (A), in addition to the above, the descriptions in paragraphs 0013 to 0041 of JP 2021-084942 A, the descriptions in paragraphs 0040 to 0073 of JP 2019-035001 A, the descriptions in paragraphs 0016 to 0043 of JP 2018-103518 A, the descriptions in paragraphs 0011 to 0048 of WO 2021 / 090823 A, and the descriptions in paragraphs 0011 to 0043 of JP 2019-156942 A can be referred to, the contents of which are incorporated herein by reference.

[0016] The proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 97% by mass or more. By making it equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be further improved. In addition, the proportion of the polycarbonate resin (A) in the resin composition of this embodiment is preferably 99% by mass or less. The resin composition of the present embodiment may contain only one type of polycarbonate resin (A), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0017] <Metal salt flame retardant (B)> The resin composition of the present embodiment contains a metal salt flame retardant (B). By containing the metal salt flame retardant, a molded article having excellent flame retardancy can be obtained. The metal salt flame retardant (B) is preferably an alkali metal salt of an organic acid and / or an alkaline earth metal salt of an organic acid, and more preferably an alkali metal salt of an organic acid. Examples of the metal salt flame retardant (B) include metal sulfonates, metal carboxylates, metal borates, metal phosphates, and metal sulfonimides. From the viewpoint of thermal stability, metal sulfonates and metal sulfonimides are preferred, and metal sulfonates are more preferred.

[0018] Examples of the alkali metal constituting the alkali metal salt include lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), etc., and among these, sodium, potassium, and cesium are preferred, sodium and potassium are more preferred, and potassium is even more preferred.

[0019] Preferable examples of the alkali metal sulfonate include alkali metal salts of fluorine-containing aliphatic sulfonic acids and / or aromatic sulfonic acids. Specific examples of preferable ones among them include alkali metal salts of fluorine-containing aliphatic sulfonic acids having at least one C—F bond in the molecule, such as potassium perfluorobutanesulfonate (potassium nonafluorobutanesulfonate), lithium perfluorobutanesulfonate, sodium perfluorobutanesulfonate, cesium perfluorobutanesulfonate, potassium trifluoromethanesulfonate, lithium trifluoromethanesulfonate, sodium trifluoromethanesulfonate, and cesium trifluoromethanesulfonate; dipotassium diphenylsulfone-3,3'-disulfonate, potassium diphenylsulfone-3-sulfonate, sodium benzenesulfonate, (poly)styrenesulfonate, and the like. Examples of aromatic sulfonate alkali metal salts having at least one aromatic group in the molecule include sodium toluenesulfonate, sodium paratoluenesulfonate, (branched) sodium dodecylbenzenesulfonate, sodium trichlorobenzenesulfonate, potassium benzenesulfonate, potassium styrenesulfonate, (poly)potassium styrenesulfonate, potassium paratoluenesulfonate, (branched) potassium dodecylbenzenesulfonate, potassium trichlorobenzenesulfonate, cesium benzenesulfonate, (poly)cesium styrenesulfonate, cesium paratoluenesulfonate, (branched) cesium dodecylbenzenesulfonate, and cesium trichlorobenzenesulfonate.

[0020] Preferred examples of the sulfonyl imide alkali metal salt include lithium bisfluorosulfonylimide, lithium bistrifluoromethylsulfonylimide, lithium bispentafluoroethylsulfonylimide, lithium bisheptafluoropropylsulfonylimide, lithium bisnonanefluorobutylsulfonylimide, sodium bisfluorosulfonylimide, sodium bistrifluoromethylsulfonylimide, sodium bispentafluoroethylsulfonylimide, sodium bisheptafluoropropylsulfonylimide, sodium bisnonanefluorobutylsulfonylimide, potassium bisfluorosulfonylimide, potassium bistrifluoromethylsulfonylimide, potassium bispentafluoroethylsulfonylimide, potassium bisheptafluoropropylsulfonylimide, and potassium bisnonanefluorobutylsulfonylimide.

[0021] For other alkali metal salts, refer to paragraphs 0069 to 0078 of JP2015-117298A, the contents of which are incorporated herein by reference.

[0022] The content of the metal salt flame retardant (B) in the resin composition of this embodiment is 0.01 parts by mass or more, preferably 0.03 parts by mass or more, more preferably 0.04 parts by mass or more, even more preferably 0.05 parts by mass or more, and even more preferably 0.06 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the formation of a carbonized layer during combustion of the polycarbonate resin can be promoted, and the flame retardancy can be further improved. In addition, the content of the metal salt flame retardant (B) is 0.3 parts by mass or less, preferably 0.25 parts by mass or less, more preferably 0.2 parts by mass or less, even more preferably 0.15 parts by mass or less, even more preferably 0.12 parts by mass or less, and even more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or less than the upper limit, the flame retardant effect tends to be more effectively exhibited, despite the reduction in the content of the metal salt flame retardant (B). The resin composition of the present embodiment may contain only one type of metal salt flame retardant (B), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0023] The resin composition of the present embodiment may or may not contain a flame retardant other than the metal salt flame retardant (B). Examples of the flame retardant other than the metal salt flame retardant (B) include phosphorus-based flame retardants and halogen-based flame retardants. An example of the resin composition of the present embodiment is one that is substantially free of flame retardants other than the metal salt flame retardant (B). "Substantially free" means that the content of flame retardants other than the metal salt flame retardant (B) among the flame retardants contained in the resin composition is 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less.

[0024] <Anti-dripping agent (C)> The resin composition of the present embodiment may contain an anti-dripping agent (C). The anti-dripping agent (C), also called an anti-dripping agent, is preferably a fibril-forming fluoropolymer, which is easily dispersed in the resin composition and tends to bond polymers together to form a fibrous structure. The fluoropolymer capable of forming fibrils has an extremely high molecular weight, preferably 1 to 10 million, and shows a tendency to bond fluoropolymers together to form fibers by external action such as shear force. Preferred fluoropolymers include tetrafluoroethylene (TFE) resin, perfluoroalkoxy (PFA) resin, fluorinated ethylene propylene (FEP) resin, etc., and particularly preferred is polytetrafluoroethylene.

[0025] Examples of fluoropolymers capable of forming fibrils include Teflon (registered trademark) 6J manufactured by Mitsui-DuPont Fluorochemicals Co., Ltd. and Polyflon manufactured by Daikin Industries, Ltd.

[0026] It is also preferable to use the fluoropolymer in the form of an aqueous dispersion. This dispersion is an aqueous dispersion produced by adding a surfactant to a fluororesin latex obtained by normal emulsion polymerization, and concentrating and stabilizing the mixture. The content of the fluoropolymer in the aqueous dispersion is preferably 20 to 80% by mass, particularly preferably 30 to 70% by mass. Examples of aqueous dispersions of polytetrafluoroethylene include Teflon (registered trademark) 30J manufactured by Mitsui DuPont Fluorochemicals, Fluon D-1 manufactured by Daikin Industries, Ltd., and polytetrafluoroethylene polymers having a multilayer structure obtained by polymerizing vinyl monomers, such as Metablen A-3800 manufactured by Mitsubishi Rayon Co., Ltd.

[0027] The fibril-forming fluoropolymer preferably has a primary particle size in the range of 0.05 to 1.0 μm, more preferably 0.1 to 0.5 μm. In the resin composition, the fluoropolymer is preferably in the form of fibrils having a thickness of 0.5 μm or less, and the fibrils preferably exist in a network structure and / or in a branched form.

[0028] The content of the anti-dripping agent (C) in the resin composition of this embodiment is 0 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.07 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the drip prevention effect tends to be effectively exhibited. In addition, the content of the anti-dripping agent (C) is 1 part by mass or less, preferably 0.7 parts by mass or less, and more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or less than the upper limit, the mechanical strength of the obtained molded product tends to be improved, and the appearance also tends to be improved. The resin composition of the present embodiment may contain only one type of anti-dripping agent (C), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0029] <Inorganic particles (D)> The resin composition of the present embodiment contains inorganic particles (D) having a thermal conductivity of 15 W / m K or more and an average particle size of 4 μm or less. By containing such inorganic particles (D), a resin composition having excellent flame retardancy after treatment in a moist heat environment and impact resistance in a low temperature environment can be obtained. The thermal conductivity of the inorganic particles (D) used in this embodiment is 15 W / m·K or more, preferably 18 W / m·K or more, more preferably 20 W / m·K or more, and even more preferably 23 W / m·K or more. By making it equal to or more than the lower limit, the early flame extinguishing effect during combustion after the moist heat environment treatment tends to be improved. In addition, the upper limit of the thermal conductivity is not particularly set, but is preferably 500 W / m·K or less, more preferably 400 W / m·K or less, and even more preferably 350 W / m·K or less. When the resin composition of the present embodiment contains two or more types of inorganic particles (D), the thermal conductivity is preferably such that the weighted average value of the thermal conductivity of each inorganic particle (D) falls within the above range.

[0030] The inorganic particles (D) have an average particle size of 4 μm or less, preferably 3.5 μm or less, and may be 2.0 μm or less, 1.0 μm or less, or 0.8 μm or less depending on the application. By making it below the upper limit, high impact resistance tends to be obtained even in a low temperature environment. In addition, the lower limit of the average particle size of the inorganic particles (D) is not particularly set, but 0.01 μm or more is practical, and even if it is 0.1 μm or more, the required performance is sufficiently satisfied. The average particle size of the inorganic particles (D) is the median size (D50).

[0031] The type of the inorganic particles (D) is not particularly limited, but is preferably a nitride, more preferably contains at least one selected from the group consisting of boron nitride, silicon carbide, and silicon nitride, and even more preferably contains boron nitride.

[0032] The inorganic particles (D) may be oxides, but are preferably not oxides (do not contain oxygen atoms). By not containing oxygen atoms, the burning time after immersion in hot water can be shortened.

[0033] The content of the inorganic particles (D) in the resin composition of this embodiment is 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, even more preferably 0.2 parts by mass or more, even more preferably 0.25 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or more than the lower limit, the flame retardancy after the moist heat environment treatment tends to be further improved. In addition, the upper limit of the content of the inorganic particles (D) is 3 parts by mass or less, preferably 2.5 parts by mass or less, more preferably 2 parts by mass or less, even more preferably 1.5 parts by mass or less, even more preferably 1 part by mass or less, and even more preferably 0.9 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making it equal to or less than the upper limit, high impact resistance tends to be obtained even in a low temperature environment. The resin composition of the present embodiment may contain only one type of inorganic particles (D), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0034] In addition, in the resin composition of this embodiment, the mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is preferably 0.03 or more, more preferably 0.05 or more, and even more preferably 0.08 or more. By making it equal to or more than the lower limit, the early flame-extinguishing effect at the time of combustion after the moist heat environment treatment tends to be improved. In addition, the upper limit of the mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is preferably 0.5 or less, more preferably 0.4 or less, even more preferably 0.35 or less, even more preferably 0.28 or less, and even more preferably 0.2 or less. By making it equal to or less than the upper limit, the early flame-extinguishing effect at the time of combustion after the moist heat environment treatment tends to be improved.

[0035] <Elastomer (E)> The resin composition of the present embodiment contains an elastomer (E). The elastomer (E) is preferably a copolymer obtained by graft-copolymerizing a rubber component with a monomer component copolymerizable therewith. The method for producing such a graft copolymer may be any of bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., and the copolymerization method may be one-stage grafting or multi-stage grafting.

[0036] The rubber component generally has a glass transition temperature of 0° C. or lower, preferably −20° C. or lower, and more preferably −30° C. or lower. The lower limit of the glass transition temperature is, for example, −100° C. or higher. Specific examples of the rubber component include polybutadiene rubber, polyisoprene rubber, polyalkyl acrylate rubber such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymer, silicone rubber such as organopolysiloxane rubber, butadiene-acrylic composite rubber, IPN composite rubber made of organopolysiloxane rubber and polyalkyl acrylate rubber, styrene-butadiene rubber, ethylene-α-olefin rubber such as ethylene-propylene rubber, ethylene-butene rubber, and ethylene-octene rubber, ethylene-acrylic rubber, and fluororubber. These may be used alone or in combination of two or more. Among these, polybutadiene rubber, polyalkyl acrylate rubber, IPN composite rubber made of organopolysiloxane rubber and polyalkyl acrylate rubber, and styrene-butadiene rubber are preferred from the standpoint of mechanical properties and surface appearance.

[0037] Specific examples of the monomer component that can be graft-copolymerized with the rubber component include aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, from the standpoint of mechanical properties and surface appearance, aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, and (meth)acrylic acid compounds are preferred, and (meth)acrylic acid ester compounds are more preferred. Specific examples of the (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate.

[0038] The elastomer (E) used in this embodiment preferably contains a core / shell type graft copolymer in terms of impact resistance and surface appearance. Among them, a core / shell type graft copolymer is preferred, which is made of at least one rubber component selected from polybutadiene-containing rubber, polybutyl acrylate-containing rubber, and IPN-type composite rubber made of organopolysiloxane rubber and polyalkyl acrylate rubber as a core layer, and a shell layer formed by copolymerizing (meth)acrylic acid ester around the core layer, and a core / shell type elastomer having a butadiene-based rubber as a core is particularly preferred. In the above-mentioned core / shell type graft copolymer, one containing 40% by mass or more of the rubber component is preferred, and one containing 60% by mass or more is more preferred. Also, one containing 10% by mass or more of the (meth)acrylic acid component is preferred.

[0039] Preferred specific examples of these core / shell type graft copolymers include acrylonitrile-butadiene-styrene copolymers (ABS), methyl methacrylate-butadiene-styrene copolymers (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymers (MABS), methyl methacrylate-butadiene copolymers (MB), methyl methacrylate-acrylic rubber copolymers (MA), methyl methacrylate-acrylic rubber-styrene copolymers (MAS), methyl methacrylate-acrylic-butadiene rubber copolymers, methyl methacrylate-acrylic-butadiene rubber-styrene copolymers, methyl methacrylate-(acrylic-silicone IPN rubber) copolymers, etc., with methyl methacrylate-butadiene copolymers (MB) being preferred. Such rubbery polymers may be used alone or in combination of two or more. In addition to the above, as the elastomer (E), those described in paragraphs 0068 to 0079 of JP 2019-123809 A can be used, the contents of which are incorporated herein by reference.

[0040] When the resin composition of the present embodiment contains the elastomer (E), the content thereof is 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin (A). By making the content equal to or more than the lower limit, the impact resistance of the obtained molded article tends to be improved. In addition, the upper limit of the content of the elastomer (E) is 5 parts by mass or less, preferably 4.5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3.5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2.5 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By making the content equal to or less than the upper limit, the surface hardness, heat resistance, rigidity, etc. of the obtained molded article tend to be improved. The resin composition of the present embodiment may contain only one type of elastomer (E), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0041] <Stabilizer (F)> The resin composition of the present embodiment may contain a stabilizer (F). The stabilizer (F) may include a heat stabilizer or an antioxidant. Examples of the stabilizer (F) include phenol-based, amine-based, phosphorus-based, and thioether-based stabilizers. Among these, in the present embodiment, phosphorus-based heat stabilizers and / or phenol-based antioxidants are preferred.

[0042] Any known phosphorus-based heat stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0043] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," and "ADK STAB HP-10" manufactured by ADEKA Corporation, "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.

[0044] As the phenol-based antioxidant, a hindered phenol-based antioxidant is preferably used. Specific examples of hindered phenol-based antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 4,6-bis(octyl butylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0045] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol-based antioxidants include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.

[0046] The content of the stabilizer (F) in the resin composition of this embodiment is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin (A). By setting the content of the stabilizer (F) within the above range, the effect of adding the stabilizer is more effectively exhibited. The resin composition of the present embodiment may contain only one type of stabilizer (F), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0047] <Release agent (G)> The resin composition of the present embodiment may contain a release agent (G). Examples of the release agent (G) include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and light amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, and esters of aliphatic carboxylic acids and alcohols are preferred, and esters of aliphatic carboxylic acids and alcohols are more preferred.

[0048] Examples of the ester of an aliphatic carboxylic acid and an alcohol include fatty acid esters such as saturated or unsaturated monovalent or divalent aliphatic carboxylic acid esters, glycerin fatty acid esters, sorbitan fatty acid esters, and partially saponified products thereof, etc. Among them, mono- or di-fatty acid esters composed of fatty acids having preferably 11 to 28 carbon atoms, more preferably 17 to 21 carbon atoms, and alcohols are preferred.

[0049] Examples of fatty acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, azelaic acid, etc. The fatty acid may also be alicyclic. Examples of the alcohol include saturated or unsaturated monohydric or polyhydric alcohols. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, monohydric or polyhydric saturated alcohols having 30 or less carbon atoms are preferred, and aliphatic saturated monohydric or polyhydric alcohols having 30 or less carbon atoms are more preferred. Here, the term "aliphatic" includes alicyclic compounds. Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol. The above ester compound may contain an aliphatic carboxylic acid and / or an alcohol as an impurity, and may be a mixture of a plurality of compounds.

[0050] Specific examples of fatty acid ester compounds include glycerin monostearate, glycerin monobehenate, glycerin dibehenate, glycerin-12-hydroxymonostearate, sorbitan monobehenate, pentaerythritol monostearate, pentaerythritol distearate, stearyl stearate, and ethylene glycol montanic acid ester. For details about the release agent (G), in addition to the above, the descriptions in paragraphs 0055 to 0061 of JP 2018-095706 A and the descriptions in paragraphs 0106 to 0115 of JP 2015-117298 A can be referred to, the contents of which are incorporated herein by reference.

[0051] When the resin composition of the present embodiment contains a release agent (G), the content thereof in the resin composition is preferably 0.05 to 3 mass %, more preferably 0.1 to 0.8 mass %, and further preferably 0.1 to 0.6 mass %. The resin composition of the present embodiment may contain only one type of release agent (G), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0052] <Other ingredients> The resin composition of the present embodiment may further contain other components other than those described above. Examples of other components include reinforcing materials, colorants, flame retardants other than metal salt flame retardants, flame retardant assistants, ultraviolet absorbers, fluorescent brighteners, impact resistance improvers, epoxy compounds, antifogging agents, flow improvers, plasticizers, dispersants, antibacterial agents, and antiviral agents. For details of these components, see paragraphs 0107 to 0115 of JP 2014-136710 A, paragraphs 0106 to 0128 of JP 2015-117298 A, paragraphs 0055 to 0061 of JP 2018-095706 A, and paragraphs 0047 to 0103 of WO 2021 / 241471 A. The contents of these components are incorporated herein by reference. When contained, the content of the above other components is, for example, 0.001 mass% or more and, for example, 5.0 mass% or less, preferably 3.0 mass% or less, and more preferably 1.0 mass% or less, based on the mass of the resin composition. In the resin composition of this embodiment, the polycarbonate resin (A), the metal salt flame retardant (B), the anti-dripping agent (C), the inorganic particles (D) and the elastomer (E) preferably account for 95 mass% or more of the resin composition, and more preferably account for 97 mass% or more. Furthermore, the total of the polycarbonate resin (A), the metal salt flame retardant (B), the anti-dripping agent (C), the inorganic particles (D), the elastomer (E), the stabilizer (F) and the release agent (G) preferably accounts for 97% by mass or more of the resin composition, and more preferably accounts for 99% by mass or more.

[0053] <Physical properties of resin composition> The resin composition of the present embodiment can provide a molded product having excellent impact resistance. In particular, the resin composition can be used to mold an ISO test piece having a thickness of 3 mm, and the notched Charpy impact strength at 23° C. measured according to ISO179-1 is 50 kJ / m 2 It is preferable that the concentration is 60 kJ / m or more. 2 More preferably, it is 65 kJ / m or more. 2The upper limit of the notched Charpy impact strength is not particularly limited, but is preferably 90 kJ / m 2 The following is practical. Furthermore, the resin composition of the present embodiment can provide a molded product having excellent impact resistance at low temperatures. In particular, the resin composition can be used to mold an ISO test piece having a thickness of 3 mm, and the notched Charpy impact strength at -30°C measured according to ISO179-1 is 40 kJ / m 2 It is preferable that the concentration is 45 kJ / m or more. 2 More preferably, it is 50 kJ / m or more. 2 The upper limit of the notched Charpy impact strength is not particularly limited, but is preferably 80 kJ / m 2 The following is practical.

[0054] Furthermore, the resin composition of the present embodiment can have excellent flame retardancy even after treatment in a moist heat environment. Specifically, the resin composition of this embodiment is molded into a UL test specimen having a length of 125 mm, a width of 13 mm, and a thickness of 1.5 mm, and the total flame burning time measured in accordance with the UL-94 test after immersing it in hot water at a temperature of 82° C. for 168 hours is preferably 50 seconds or less, more preferably 49 seconds or less, even more preferably 45 seconds or less, and even more preferably 40 seconds or less. The lower limit of the total burning time is preferably 0 seconds, and 1 second or more is practical.

[0055] <Production of Resin Composition> The method for producing the resin composition of this embodiment is not limited, and a wide variety of known methods for producing resin compositions can be used, including a method in which the polycarbonate resin (A), the metal salt flame retardant (B), the anti-dripping agent (C), the inorganic particles (D) and the elastomer (E), as well as other components that are blended as necessary, are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The temperature for melt-kneading is not particularly limited, but is usually in the range of 240 to 320°C.

[0056] One form of the resin composition of the present embodiment is pellets. The resin composition or pellets of this embodiment are molded into various molded articles. That is, the molded article of this embodiment is a molded article formed from the resin composition or pellets of this embodiment. The molding method of the molded article is not particularly specified, but examples thereof include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted and other hollow molding methods, molding methods using a heat-insulating mold, molding methods using a rapidly heated mold, foam molding (including supercritical fluids), insert molding, IMC (in-mold coating molding) molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, and the like, among which injection molding is preferred.

[0057] The shape of the molded product of the present embodiment is not particularly limited and can be appropriately selected depending on the application and purpose of the molded product. Examples of the shape include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, polygonal, irregularly shaped, hollow, frame-like, box-like, panel-like, and special shapes.

[0058] The molded article of the present embodiment is preferably used as structural member components, portable electronic device components, vehicle and medical device components, other electronic components including electric circuits and their housings, food and pharmaceutical containers, and composite materials for forming these. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0060] 1.Raw materials The following raw materials were used:

[0061] [Table 1]

[0062] In the above table, the entries in parentheses for the (D) components indicate the average particle size and thermal conductivity, respectively. For example, D1 has an average particle size of 3 μm and a thermal conductivity of 40 W / m·k. The thermal conductivity of the inorganic particles was taken as the physical property value of the ingot of each material.

[0063] 2. Examples 1 to 17 and Comparative Examples 1 to 7 <Production of Resin Composition (Pellets)> The components shown in Table 1 were blended in the ratios (parts by mass) shown in Tables 2 to 5 and mixed in a tumbler for 20 minutes, and then fed from an upstream feeder to a twin-screw extruder (TEX30α) manufactured by Japan Steel Works, Ltd. equipped with one vent, and kneaded under conditions of a rotation speed of 200 rpm, a discharge rate of 30 kg / hour, and a barrel temperature of 280° C. The molten resin extruded in the form of strands from the extruder was quenched in a water tank and pelletized using a pelletizer to obtain pellets of a polycarbonate resin composition.

[0064] <Notched Charpy impact strength> The pellets obtained above were dried at 120°C for 5 hours, and then molded into 3mm thick ISO multipurpose test pieces using a Nissei Plastic Industrial Co., Ltd. injection molding machine "NEX80III" at a cylinder temperature of 280°C and a mold temperature of 80°C. In accordance with ISO179-1 and ISO179-2, the notched Charpy impact strength (unit: kJ / m) was measured using ISO multipurpose test pieces at 23℃ and -30℃. 2 ) was measured.

[0065] <Flame retardancy evaluation UL94 test> The pellets obtained by the above method were dried at 120°C for 5 hours, and then injection molded using a Sumitomo Heavy Industries SE100DU injection molding machine at a cylinder temperature of 280°C and a mold temperature of 80°C to form UL test specimens with a length of 125 mm, a width of 13 mm, and a thickness of 1.5 mm. Flame retardancy was evaluated by immersing the UL test specimens obtained above in hot water at 82°C for 168 hours, wiping the specimens, and conducting the evaluation in accordance with the UL94 test (combustion test for plastic materials for equipment parts) established by Underwriters Laboratories (UL) in the United States. Five specimens were exposed to flame a total of 10 times, and the total flame burning time (seconds) was calculated.

[0066] [Table 2]

[0067] [Table 3]

[0068] [Table 4]

[0069] [Table 5]

[0070] As is clear from the above results, the flame retardancy of the molded article formed from the resin composition of the present invention was stabilized after the treatment in a humid and hot environment. In addition, despite the incorporation of inorganic particles, the decrease in Charpy impact strength at low temperatures was effectively suppressed.

Claims

1. For 100 parts by mass of polycarbonate resin (A), A metal salt flame retardant (B) of 0.01 parts by mass or more and 0.3 parts by mass or less; A dripping prevention agent (C) of 0 parts by mass or more and 1 part by mass or less; 0.05 parts by mass or more and 3 parts by mass or less of inorganic particles (D) having a thermal conductivity of 15 W / m · K or more and an average particle diameter of 4 μm or less; 0.01 parts by mass or more and 5 parts by mass or less of an elastomer (E); A resin composition comprising:

2. The resin composition according to claim 1, wherein the inorganic particles (D) contain at least one selected from the group consisting of boron nitride, silicon carbide, and silicon nitride.

3. The resin composition according to claim 1 or 2, wherein the elastomer (E) comprises a core / shell type graft copolymer.

4. The resin composition according to claim 1 or 2, wherein the mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is 0.03 to 0.

5.

5. The inorganic particles (D) contain at least one selected from the group consisting of boron nitride, silicon carbide, and silicon nitride, The elastomer (E) comprises a methyl methacrylate-butadiene copolymer, The resin composition according to claim 1, wherein the mass ratio (B) / (D) of the metal salt flame retardant (B) to the inorganic particles (D) is 0.03 to 0.

5.

6. A pellet of the resin composition according to claim 1, 2 or 5.

7. A molded article formed from the resin composition according to claim 1, 2 or 5.

8. A molded article formed from the pellets of claim 6.

Citation Information

Patent Citations

  • Flame-retardant aromatic polycarbonate resin composition

    JP2004002750A